Structural rationale to understand the effect of disease-associated mutations on Myotubularin - Teerna Bhattacharyya; Avishek Ghosh; Shailya Verma; Padinjat Raghu; Ramanathan Sowdhamini (Current Research in Structural Biology, 2023)
Myotubularin or MTM1 is a lipid phosphatase that regulates vesicular trafficking in the cell. The MTM1 gene is mutated in a severe form of muscular disease, X-linked myotubular myopathy or XLMTM, affecting 1 in 50,000 newborn males worldwide. There have been several studies on the disease pathology of XLMTM, but the structural effects of missense mutations of MTM1 are underexplored due to the unavailability of a crystal structure. MTM1 consists of three domains-a lipid-binding N-terminal GRAM domain, the phosphatase domain and a coiled-coil domain which aids dimerisation of Myotubularin homologs. While most mutations reported to date map to the phosphatase domain of MTM1, the other two domains on the sequence are also frequently mutated in XLMTM. To understand the overall structural and functional effects of missense mutations on MTM1, we curated several missense mutations and performed in silico and in vitro studies. Apart from significantly impaired binding to substrate, abrogation of phosphatase activity was observed for a few mutants. Possible long-range effects of mutations from non-catalytic domains on phosphatase activity were observed as well. Coiled-coil domain mutants have been characterised here for the first time in XLMTM literature.